UPAYA PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR PKN MELALUI METODE PEMBELAJARAN TAKE AND GIVE KELAS IV - Rumpakha, Vidya; Dwikurnaningsih, Yari (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2017)
Abstract: The background of this study is the low activeness and student learning outcomes in the subject of Civics Education (Civics) of the fourth grade in the fourth semester class of government, there are 14 out of 22 students whose value does not reach Minimal Completeness Criteria (KKM) (≥ 70). The aims of this study is to determine the improvement of student activeness and civics education learning outcomes through the Take and Give Methods Learning fourth graders SDN 1 Buntu Kejajar District Wonosobo Regency. The type of this research is a classroom action research which is conducted in 2 cycles, each cycle consists of 3 stages: 1) Action planning; 2) Implementation of action and Observation; 3) Reflection. Technique of collecting data in the form of test and non test technique, with research instrument in the form of item and observation sheet equipped with rubric measurement of student activeness. The analysis technique used is descriptive comparative technique that is analysis technique that compare the result of pre cycle learning, cycle I, and cycle II. This is indicated by the improvement in student learning outcomes, namely cycle I has increased learning outcomes from the average prasiklus 59.81 to 68.04 (77.27%), the level of student activeness using the likert scale is 70.3 (active). Cycle II has increased learning outcomes from the average cycle I 68,04 to 75,19 (86,36%), student activeness level using likert scale is 78,3 (very active). From this study can be concluded by applying the Take and Give model can significantly improve the learning outcomes and the activity of students of Civics subjects in fourth grade students.Keywords: Student Activeness, Civic Learning Outcomes, Take and Give Learning Methods Abstrak: Latar belakang penelitian ini adalah rendahnya keaktifan siswa dan hasil belajar PKn. Terdapat 14 dari 22 siswa yang nilai PKn tidak mencapai KKM ( ≥ 70). Penelitian ini bertujuan untuk mengetahui peningkatan keaktifan siswa dan hasil belajar PKn melalui metode pembelajaran Take and Give siswa kelas IV semester II SDN 1 Buntu Kecamatan Kejajar Kabupaten Wonosobo. Jenis penelitian ini adalah penelitian tindakan kelas yang prosedur penelitian dilakukan sebanyak 2 siklus, masing-masing siklus terdiri dari 3 tahapan yaitu 1) Perencanaan tindakan; 2) Pelaksanaan tindakan dan Observasi; 3) Refleksi. Teknik pengumpulan data berupa teknik tes dan non tes, dengan instrumen penelitian berupa butir soal dan lembar observasi yang dilengkapi dengan rubrik pengukuran keaktifan siswa. Teknik analisis yang digunakan adalah teknik deskriptif komparatif yaitu teknik analisis yang membandingkan hasil belajar pra siklus, siklus I, dan siklus II. Hal ini ditunjukkan dengan peningkatan hasil belajar siswa yaitu siklus I mengalami peningkatan hasil belajar dari rata-rata pra siklus 59,81 menjadi 68,04 (77,27%), tingkat keaktifan siswa menggunakan skala likert adalah 70,3 (aktif). Siklus II mengalami peningkatan hasil belajar dari rata-rata siklus I 68,04 menjadi 75,19 (86,36%), tingkat keaktifan siswa menggunakan skala likert adalah 78,3 (sangat aktif). Dari penelitian ini dapat disimpulkan dengan menerapkan metode pembelajaran Take and Give secara signifikan dapat meningkatkan hasil belajar dan keaktifan siswa mata pelajaran PKn pada siswa kelas IV.Kata Kunci: Keaktifan Siswa, Hasil Belajar PKn, Metode Pembelajaran Take and Give